Bartolomeo Miniatore e l'Umanesimo volgare: con edizione critica del "Formulario di esordi ed epistole missive e responsive per Giacomo Bolognini" - Amendola, Cristiano (Testi: Antichità, Medioevo e Umanesimo, 2022)
During the fifteenth century, the evolution of the structures of the Italian states and the stabilization of their diplomatic relations led to a hypertrophic increase in the use of the letters. In that context, the collections of exempla exordiorum composed by the Ferrarese treatise writer and illuminator Bartolomeo di Benincà (Ferrara, ca. 1420 - ?, before 1485) responded to the political élites who, speaking and writing in ancient vernacular Italian, wishing to represent themselves through the instruments of the language. As author and collector of texts, Bartolomeo recorded the best examples of these practices on refined parchment codes, offering a useful tool for anyone wishing to compose letters in vernacular similar in elegance to those of the then much more prestigious Latin models. By outlining a stylistic proposal for literary prose in ancient Italian vulgar, he carried out a refined critical operation. Furthermore, with his collections of models in vernacular, he profoundly innovated the characters of the ars dictaminis. This volume offers the critical edition of one of Bartolomeo's collections, preceded by an extensive study focussed on the historical and cultural context.